A genre analysis of English editorials in The Bangkok Post / Ilham Binharong - Ilham , Binharong (2018)
Genre analysis has been focusing on textual analysis both at the macro and micro levels. Steady interest amongst researchers in the field of linguistics and applied linguistics have looked at other scope particularly within the scope of professional genres. This study which embraces the genre theory of the ESP school looks at the rhetorical moves of editorials in order to identify its communicative purposes. Specifically, the study aimed to explore how editorial writers use language to achieve their communicative purposes by investigating the move structure as well as its interactional metadiscourse in the editorial articles. Fifty editorial articles collected from ‘The Bangkok Post’ were analyzed based on the framework adapted from Bhatia’s (1993) and Tongsibsong (2012) models in order to define the rhetorical moves and strategies in the study. Additionally, Hyland’s (2005) interpersonal metadiscourse model was applied to investigate interactional markers in the articles. The analysis showed that the communicative purposes of editorials are mainly to persuade and motivate readers to agree with the newspaper’s position as well as to recommend and suggest the readers to do as the newspaper editorial writers offer. Further analysis points out that Presenting headline, Presenting the case, Justifying or refuting event, and Articulating a position are obligatory moves. Furthermore, the investigation of interactional markers revealed that hedges are the highest item in the corpus which is 39.85%. The categories of engagement marker, boosters, attitude marker denoted 25.78%, 19.83%, and 11.99% occurrences respectively. Finally, the selfmentions category is the least occurred in the text, 2.55%. This study is significant to enhance the teaching of writing to ESL/EFL learners in both the academic and professional contexts. The findings may heighten the awareness of ESP learners on the importance of using appropriate rhetorical moves, strategies as well as interactional metadiscourse markers in achieving persuasive stance in the writing of editorials